Digital and remote behavioral therapies for treating tic disorders: Recent advances and next steps - Khan, Kareem; Hollis, Chris; Murphy, Tara; Hall, Charlotte L. (Frontiers in Psychiatry, 2022)
The rapid expansion of access to and engagement with digital technology over the past 15 years has transformed the potential for remote delivery of evidence-based digital health interventions (DHIs). Digital and remote behavioral interventions have the potential to address current gaps in the provision of evidence-based therapies in healthcare services. As the lack of access to behavioral treatments for people with tic disorders is a pressing issue across the world, there is great potential for DHIs to close this treatment gap. Here, we present a critical synthesis of the recent key advances in the field of digitally delivered, remote therapy for tics, outlining the research evidence for the clinical and cost-effectiveness and acceptability of digital or remotely delivered therapy. We found five trials aimed at reducing tic severity in children and young people and one trial for adults. The evidence supports the clinical utility of DHIs to deliver tic therapies, which shows promise in being clinically effective compared to an active control. Furthermore, DHIs in trials show good adherence and engagement and are acceptable to patients. The role of human support (including therapists and parents for young people) is likely to be important to encourage adherence. DHIs, where the main therapeutic content is delivered via web-based chapters, are likely to reduce clinical time, and maintain intervention fidelity, but further research is required to understand cost-effectiveness. Despite utilizing randomized controlled trials, only two trials were sufficiently powered to address efficacy and only one trial explored contextual factors that may influence engagement. Moreover, only one trial followed patients for >12 months, thus further long-term follow-ups are required. Specifically, we note that despite an emerging evidence base, DHIs for tics are yet to be routinely implemented in healthcare provision in any country. Drawing on the existing evidence, we conclude by proposing a stepped care model, in which digital therapy is implemented as a widely accessible first-line treatment using a purely online or therapist-supported approach.